Strategic Relationship Value and Supply Chain Resilience: Decoupling Satisfaction from Loyalty in the Indonesian Automotive B2B Sector - Veronika Nadia Andriyani; Anny Nurbasari (Yayasan Cerdas Pedia Indonesia, 2026)
As the Indonesian automotive industry faces intensifying competition within the ASEAN Economic Community, specifically from Thailand, the strategic imperative has shifted from price leadership to supply chain resilience. This study investigates the economic efficacy of relationship value in driving customer loyalty within the Business-to-Business (B2B) spare parts sector in West Java, hypothesizing trust, commitment, and satisfaction as critical mediators. Utilizing a Structural Equation Modeling (SEM) approach with data from 211 decision-makers, the research challenges the canonical Service-Profit Chain theory in emerging markets. The empirical results demonstrate that while relationship value significantly bolsters trust and commitment, a divergence from Western models is observed: customer satisfaction does not significantly influence loyalty (CR < 1.96). This anomaly suggests that in the Indonesian B2B context, retention is driven by structural commitments and calculated relationship value rather than affective satisfaction. These findings imply that to sustain competitive advantage, firms must prioritize the engineering of strategic partnerships over satisfaction metrics, offering a new perspective on industrial retention strategies in developing economies.